Bitcoin as an alternative digital currency.Exploring the publics’ perception vs experts - S. Papathanasiou; N. Papamatthaiou; D. Balios (International Journal of Financial Engineering and Risk Management, 2019)
Νumerous attempts have been made to explain and classify Bitcoin. The different opinions of eminent economists on the subject have raised a series of questions: What is the public’s notion of the digital currency? Would a general use of a digital currency be acceptable and if so, what kind of use would that be? Does the view of the experts on the subject conform with that of the layman individual? Our goal is to find out if the view of the public coincides with the opinion of the experts on the subject and to determine if is information can be implemented in order to establish a use of Bitcoin in our everyday lives, apart from the specialized use it has to date. During the first stage of this research, methods and rules of analysis such as descriptive statistics and tables and charts were used. Firstly, a questionnaire was used and secondly, the answers were gathered, classified and added up according to the participants’ choices. During the second stage the data was collected with the use of random sampling, while various techniques, such as simple and multiple regressions were utilized for analyzing the results. The conclusion which has been obtained is that the public perceives Bitcoin differently than the experts do. Individuals believe that Bitcoin is mainly a means of transactions/payments, contrary to the experts’ opinion, which is that it is foremost an investment asset. Additionally, we may perceive a convergence between the view of public and that of the experts on the adoption of Bitcoin technology by existing trading systems.